PENINGKATAN LITERASI DIGITAL DALAM PENDIDIKAN MELALUI PELATIHAN PEMANFAATAN APLIKASI GOOGLE SUITE - Tjandrarini, Tjandrarini; Tanuwijaya, Haryanto; Kisworo, Angen Yudho; Budiardjo, Hardman; Koentjoro, Edo Yonatan (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aimed to improve digital literacy among teachers at Yayasan Barunawati Biru Surabaya through training on the use of Google Suite. The training was conducted offline and attended by 23 teachers, using a hands-on approach with an applicative module. The sessions covered Google Chrome, Gmail, Google Groups, Google Calendar, Google Drive, and Google Meet. After the training, participants were asked to give feedback using a Likert-scale questionnaire that focused on five main areas. Results showed an average participant satisfaction score of 4.57 out of 5, indicating a very high level of satisfaction. Participant feedback suggested the training was beneficial, with recommendations to extend its duration and cover more advanced topics. The program proved effective in enhancing teachers’ digital competencies to support technology-based learning.